Metodologias ativas no ensino de história: sala de aula invertida aplicada no ensino médio na Escola Marista de Santa Maria - RS - Glufke, Carlos Eduardo Cossettin (2019)
This work has the objective of amplifying the discussion regarding the use of active methodologies in high school teaching by Rede Marista de Educação Básica. The flipped classroom is one possibility towards this as it represents an opportunity of modernizing the teaching and learning in which human and material resources interact to implement active theoretical methodological approaches. It is assumed that new methodologies and practices associated with the humanities are needed, especially in history teaching. In this opportunity, initially, a study about the history teaching, especially in Brazil, was conducted. This study considered the history of Instituto Marista without disregarding the documents which guide its Basic Education. These references were searched with the objective of finding a theoretical basis to apply active methodologies, especially the flipped classroom, to enable its application in first year high school cohorts from Colegio Marista in Santa Maria. The activities carried out served as a qualitative empirical basis, especially as reflections regarding the flipped classroom applications. The work carried out revealed that it is possible to apply the active methodology and that it has the capacity to engage the students in the proposed activities. Nonetheless, there is a need for previous preparation, not only from the teacher’s side but also from the students’ side.